Design and Development of Website-Based Sales Information System at PT. Surabaya Trading Industri - Berliando, Zuilham Ongky; Sunarto, Dewiyani; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
In the system that runs on PT. Surabaya Trading Industry, that need to be resolved. The sales process for a company takes a long time and customers have to come to the company because of the large number of orders that must be checked one by one because it is based on a lot of documents and there may be broken and unreadable. PT. Surabaya Trading Industry has difficulty in marketing and recording orders, especially in customers whose geographical location is far from the company so that customers must come to the company, this causes difficult access to facilitate customers. So that all existing orders can be managed and monitored, we need a system to manage orders. A solution is given in the form of a web-based sales information system application at PT. Surabaya Industrial Trading. Tthis application can help PT. Surabaya Trading Industry to manage order data, provide a function of stock and order monitoring that is recorded when ordering takes place so that the company can find out information about the order. The application also helps in providing order reports, income reports, and stock reports.